Squareflower, Paronychia erecta - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Squareflower is found in beach dunes, coastal grasslands, and scrub. This plant is an endemic restricted to the coastal Panhandle of Florida, counties west of the Big Bend region, and west to Louisiana. The square outline of the inflorescence is unique and makes squareflower a desirable plant for coastal landscapes. https://edis.ifas.ufl.edu/sg179